PENGEMBANGAN E-BOOK BERBASIS PENDEKATAN SAINTIFIK PADA MATERI SIKLUS HIDUP HEWAN KELAS IV SEKOLAH DASAR - Dwiputri, Sekar; Wahyudiana, Endang; Hasanah, Uswatun (Efektor, 2022)
This research creates e-book based-scientific on animal life cycle material at 4th grade Elementary School. This type of research is research and development with ADDIE model. The subjects were the fourth grade students of SDN Kebon Baru 09. The data obtained were collected through questionnaires and observation. The respondents in this research were instructional design experts, materials experts, linguists and the fourth grade students. The results showed that the feasibility of e-book based on a scientific approach were"very good" category with percentage of 96.25% from instructional design experts, 88.75% from material experts, and 92.5% from linguistic experts in the. The results of the trial to students through individual assessments were 91.25% and small group assessments were 98.52%. Based on the assessments of the experts and testing on students, it was concluded that this e-book based on a scientific approach was very adequate to be used as additional teaching material for science and animal life cycle material for 4th grade elementary school students.